The stuff of spectatorship: material cultures of film and television - Benson-Allott, Caetlin Anne (University of California Press, 2021)
Frontmatter -- Contents -- Figures -- Acknowledgments -- Introduction Material Meditations -- Chapter 1 Collecting and Recollecting Battlestar Galactica through Video's Varied Technologies of Memory -- Chapter 2 The Commercial Economy of Film History Or, Looking for Looking for Mr. Goodbar -- Chapter 3 "Let's Movie" How TCM Made a Lifestyle of Classic Film -- Chapter 4 Spirits of Cinema Alcohol Service and the Future of Theatrical Exhibition -- Chapter 5 Blunt Spectatorship Inebriated Poetics in Contemporary US Television -- Chapter 6 Shot in Black and White The Racialized Reception of US Cinema Violence -- Conclusion Expanding the Scene of the Screen -- Appendix -- Notes -- Selected Bibliography -- Index